Tata Kelola Pendidikan Islam Moderat di PTKIS: Sebuah Model Manajemen Penguatan Moderasi Beragama - Akhmad Shunhaji; Mamluatun Nafisah; Miftakhul Arif (Cetta: Jurnal Ilmu Pendidikan, 2026)
Religious moderation has become a strategic issue in Islamic higher education, as universities not only transmit knowledge but also shape students’ value orientations and socio-religious practices. However, in Private Islamic Religious Universities (PTKIS), religious moderation is often treated as a normative agenda or occasional program, limiting its sustainability. This study aims to analyze how religious moderation is institutionalized within PTKIS governance and to formulate an operational and sustainable management model for strengthening religious moderation. The research employed a qualitative multi-site case study approach across three PTKIS in Banten during the 2023/2024 academic year. Data were collected through in-depth interviews, participatory observation, and institutional document analysis, and were examined using thematic analysis with source and technique triangulation. The findings reveal that religious moderation becomes effective and sustainable when embedded within an integrated governance system through six key components: strategic orientation in institutional planning, academic and student affairs policies, instructional and academic forum design, structured student organization cadre development, participatory leadership as symbolic capital, and systematic monitoring and evaluation mechanisms. Moderation anchored in institutional structures, academic culture, and consistent leadership practices proves more durable than programmatic or ceremonial approaches. In conclusion, religious moderation in PTKIS is fundamentally a matter of institutional governance rather than merely a pedagogical concern. An integrated management model combining policy alignment, participatory leadership, dialogical campus culture, and continuous evaluation constitutes a prerequisite for cultivating a moderate religious habitus and sustaining campus harmony and stability.